CluMSy a middleware for cluster management. - Chua, Elaine Jane E. (Philippine Computing Journal)
Handling common tasks, such as listing of files or processes and manually setting up consistent software installation on all nodes of a cluster will require a lot of time and effort and may affect productivity of the cluster. Thus, interactive monitoring and management functions in a cluster environment are becoming a necessity. CluMSy is a cluster middleware that provides support for parallel programming through interactive monitoring and management functions on a cluster of independent nodes running Linux. These are classified into three (3) categories: cluster-level file management, cluster-level process management, and cluster-level account management commands. Aside from monitoring and management functions that incorporate classical UNIX commands, CluMSy also assists users in the preparation and termination of parallel program executions.